Maynard Keynes, An Economist's Biography - Seccareccia, Mario (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "Maynard Keynes: An Economist's Biography," by D. E. Moggridge.
Keywords: Biographies; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economists; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z